Aktivitas Antioksidan Formula Nano Gel Kombinasi Daun Sonneratia caseolaris dan Trigona sp. Propolis - Sabina Guseynova; Paula Mariana Kustiawan (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2024)
Sonneratia caseolaris and Kelulut propolis (Trigona sp.) are used by people to protect the face from sun exposure. Both have antioxidant potential, but until now no one has used the combination of these two natural ingredients as an antioxidant. The aims of this research were to obtain antioxidant activity from nano gel formula combination of Sonneratia caseolaris and Trigona sp Propolis extracts. The nano gel formulation was made into 3 formulations with concentrations of F1 (1:1), F2 (1:2) and F3 (2:1) by evaluating the preparation and antioxidant activity by using DPPH method. The evaluation results showed that all of the nano gel formulas were in accordance with the standard characteristics of the preparation and strong antioxidant activities with IC50 (µg/mL) result : F1 (17.568), F2 (35.112) and F3 (14.503). Based on the IC50 results, the greatest antioxidant activity was obtained in Formula 1.